Factors Associated with Postintubation Hypotension Among Patients with Suspected Sepsis in Emergency Department - Tangkulpanich P; Angkoontassaneeyarat C; Trainarongsakul T; Jenpanitpong C (Open Access Emergency Medicine, 2023)
Panvilai Tangkulpanich, Chuenruthai Angkoontassaneeyarat, Thavinee Trainarongsakul, Chetsadakon Jenpanitpong Department of Emergency Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Chetsadakon Jenpanitpong, Department of Emergency Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand, Email chetsadakon.jen@mahidol.ac.thPurpose: Postintubation hypotension (PIH) is a recognized complication that increases both in-hospital mortality and hospital length of stay. Sepsis is reportedly a factor associated with PIH. However, no study to date has examined which factors, including the intubation method, may be clinical predictors of PIH in patients with sepsis. This study aims to investigate factors associated with the occurrence of PIH in patients with suspected sepsis in emergency department.Patients and Methods: This retrospective cross-sectional study was performed over a 5-year period (January 2013–December 2017) and involved patients with suspected sepsis who underwent endotracheal intubation in the emergency department of Ramathibodi Hospital. The patients were divided into those with and without PIH, and factors associated with the occurrence of PIH were analyzed. PIH was defined as any recorded systolic blood pressure of < 90 mmHg within 60 minutes of intubation.Results: In total, 394 patients with suspected sepsis were included. PIH occurred in 106 patients (26.9%) and was associated with increased in-hospital mortality (43.00% in the PIH group vs 31.25% in the non-PIH group, P = 0.034). Multivariable logistic regression showed that the factors associated with PIH were an age of ≥ 61 years (adjusted odds ratio [aOR] 2.25; 95% confidence interval [CI] 1.14– 4.43; P = 0.019) and initial serum lactate concentration of > 4.4 mmol/L (aOR 2.00; 95% CI 1.16– 3.46; P = 0.013). Rapid sequence intubation and difference types of induction agents was unrelated to PIH.Conclusion: Monitoring the development of PIH in patients with sepsis is essential because of its correlation with higher in-hospital mortality. This is particularly critical for older individuals and those with severe infections and high initial lactate concentrations.Keywords: postintubation hypotension, sepsis, emergency department intubation